Flexible Framework For A Web Transactional Application - Abd Ghani, M. K.; Shibghatullah, A. S.; Selamat , A. (2006)
Software development project becomes difficult because of the complexity in the business requirements, rigid framework and unpredictable performance. These cause difficulties to deliver the software on time, to maintain it and to adapt to new requirements. This research proposes a Web-Based Transactional Application Architecture Framework (WTBF) to simplify the development of a complex software project by using template approach that contains assembled pieces of reusable software components. The framework provides a generalized component-based architectural template that can be reused by the users (software developer and an independent software vendor) to develop multi-tier transactional applications within a specific domain or for a new software project. One of its significant benefits is that users can concentrate on their business components development tasks instead of spending time on redeveloping basic software infrastructure from the scratch. The WTBF framework is developed by using the Java 2 Technology and the Model View Controller (MVC) is used for the architectural model.